1986
DOI: 10.1254/jjp.40.423
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Avian Pancreatic Peptide on Smooth Muscle Relaxations by Vasoactive Intestinal Peptide and Inhibitory Nerve Stimulation

Abstract: Abstract-Experimentswere carried out to investigate whether avian pancreatic peptide (APP) antagonized relaxations of vascular and gastrointestinal smooth muscles induced by vasoactive intestinal peptide (VIP) and non-adrenergic, non cholinergic inhibitory nerve stimulation using the cat submandibular gland, cat colon and dog stomach in vivo and several isolated smooth muscles in vitro. APP caused a dose-dependent inhibition of an atropine-resistant vasodilatation induced by chorda-lingual and pelvic nerve sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1988
1988
1994
1994

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The iodinated VIP was aliquoted and lyophilized under a nitrogen stream. The radioimmunoassay was carried out by the method described previously (Ito, Ohta, Nakazato, Ohga & Yanaihara, 1986). The data from standards (0-78-100 fmol) were analysed by the logit method and the best line was calculated by unweighted least squares using a personal computer (NEC9801).…”
Section: Vip Radioimmunoassay Proceduresmentioning
confidence: 99%
“…The iodinated VIP was aliquoted and lyophilized under a nitrogen stream. The radioimmunoassay was carried out by the method described previously (Ito, Ohta, Nakazato, Ohga & Yanaihara, 1986). The data from standards (0-78-100 fmol) were analysed by the logit method and the best line was calculated by unweighted least squares using a personal computer (NEC9801).…”
Section: Vip Radioimmunoassay Proceduresmentioning
confidence: 99%
“…For example, it has been shown that aPP had no effect on basal mechanical activity or on vasoactive intestinal peptide (VIP) and transmural stimulation induced relaxation of fundus muscle preparations in the guinea-pig (Ito, Ohta, Nakazato, Ohga & Yanaihara, 1986). Additionally, no effects of aPP were observed on vagally or VIP-evoked gastric relaxation in the dog (Ito et at. 1986).…”
Section: Resultsmentioning
confidence: 99%
“…Antisera to synthetic porcine VIP (Protein Institute, Osaka) conjugated to bovine serum albumin (BSA) were raised in rabbits. The antiserum (VK208) used recognized the mid-and carboxyl-terminal regions of VIP molecule (Ito, Ohta, Nakazato, Ohga & Yanaihara, 1986) and did not cross-react with the peptide histidine-isoleucine (PHI). Antisera to synthetic SP (Protein Institute, Osaka) coupled to BSA were also raised in rabbits.…”
Section: Characteristics Of Antiseramentioning
confidence: 99%
“…Peptides (VIP, 0-6 nmol; [Tyr8]SP, 5 nmol) were iodinated by chloramine T methods using 1 mCi 125NaI (Amersham). lodinated VIP was purified as described previously (Ito et al 1986). lodinated [Tyr8]SP was purified according to the method of McGregor & Bloom (1983).…”
Section: Preparation Of Iodinated Peptidesmentioning
confidence: 99%